Saccular functions differ for Meniere’s disease with and without coexisting headaches - Inui, Takaki; Kuriyama, Tatsuro; Moriyama, Kou; Shirai, Takeo; Sudo, Tomoyuki; Ayani, Yusuke; Ozaki, Akiko; Inaka, Yuko; Araki, Michitoshi; Haginomori, Shin-Ichi; Kawata, Ryo (Frontiers in Neurology, 2023)
Objectives To elucidate the differences between the cases of Meniere’s disease (MD) with and without coexisting headaches, especially migraine. The clinical characteristics and vestibular functions are compared. Subjects Fifteen patients with definite unilateral MD without headaches (MD/H−; 10 males and 5 females; mean age of 55.8 years), and 20 patients with definite unilateral MD with headaches (MD/H+; 3 males and 17 females; mean age of 54.4 years; 15 cases of migraine without aura and 5 cases of suspected migraine or tension-type headache) were enrolled. Methods The medical records, caloric test results, and cervical vestibular evoked myogenic potential (cVEMP) of the patients were reviewed. A monothermal caloric test by injection of cold water was performed, and canal paresis was assessed. cVEMP was recorded using 500 Hz short tone bursts, and the asymmetry ratio using the corrected amplitude of p13–n23 was determined. Results The patients in the MD/H− group were predominantly male, whereas more female patients were seen in MD/H+ group (p = 0.004). In the MD/H+ group, the frequency of vertigo and the dizziness handicap inventory (DHI) values were significantly higher than those in the MD/H− group (p = 0.045, <0.001, respectively). There was no statistical difference in the ages, duration of illness, or the hearing levels between both groups. The caloric testing results were abnormal for 10 of the 13 MD/H− cases, and 14 of the 16 MD/H+ cases, which revealed no significant difference between both groups. The cVEMP results revealed positive saccular dysfunction based on the asymmetry ratio of 4 of the 15 MD/H− cases, and 14 of the 20 MD/H+ cases; it was significantly more prevalent in the MD/H+ group than in the MD/H− group (p = 0.018). Multivariate analysis of sex, frequency of vertigo, DHI, and cVEMP results showed significant differences only in the cVEMP results (p = 0.049). Conclusion The present study revealed differences in patients with MD depending on the presence or absence of headaches. MD without headaches showed a significant male preponderance. MD with coexisting headaches was more associated with severe saccular dysfunctions than MD without headaches. Concomitant headache may affect the manifestations of the vestibular function, especially in the sacculus, in MD cases.